The Effectiveness of Using TikTok Social Media as a Digital Marketing Platform for Food and Beverage Products @Kiki Jupe - Shofiatus Sholihah; Faris Faris (Utan Kayu Publishing, 2025)
The effectiveness of TikTok as a digital marketing platform in promoting food and beverage products, with a case study on the TikTok account @kikijupe. The rapid development of digital technology has encouraged businesses to utilize social media as a more interactive promotional tool and reach a wider audience. TikTok, as a short video-based platform, offers a significant opportunity to build closeness between brands and consumers through creative content. The purpose of this study was to determine the effectiveness of using TikTok as a digital marketing platform for food and beverage products, @kikijupe. This study used a descriptive qualitative approach with a case study method. Data were collected through observation, documentation of the @kikijupe TikTok account's activities, and in-depth interviews with the account manager and several consumers. Analysis was conducted by reviewing uploaded content, audience interactions, and their impact on increasing sales and brand awareness. The results showed that the use of TikTok by the @kikijupe account was effective in attracting consumer attention and increasing product appeal. Strategies used included creating trend-following content, using popular music, storytelling, and collaborating with other users. In addition, interactive features such as comments, live streaming, and hashtag challenges were also utilized to expand market reach